2022
DOI: 10.1371/journal.pone.0264953
|View full text |Cite
|
Sign up to set email alerts
|

A molecular insight into the lipid changes of pig Longissimus thoracis muscle following dietary supplementation with functional ingredients

Abstract: In this work, the Longissimus thoracis pig skeletal muscle was used as a model to investigate the impact of two different diets, supplemented with n-3 polyunsaturated fatty acids from extruded linseed (L) and polyphenols from grape skin and oregano extracts (L+P), on the lipidomic profile of meat. A standard diet for growing-finishing pigs (CTRL) was used as a control. Changes in lipids profile were investigated through an untargeted lipidomics and transcriptomics combined investigation. The lipidomics identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Piasentier et al used smaller dataset sizes that averaged 24-50 individuals in each group, where diet effect on the lard composition was weighted using the PCs scores as covariates in a tri-factorial (genotype, carcass leanness, sex) covariance design (Piasentier et al, 2009). Rocchetti et al investigated the impact of different diets on the lipidomic profile of pork using 36 animals and applied both PCA and cluster analysis (Rocchetti et al, 2022). Petroman et al applied gas chromatography-mass spectrometry and PCA to evaluate the dissimilarity of Mangalitza lipid fractions in different layers of backfat with or without heat treatment (Petroman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Piasentier et al used smaller dataset sizes that averaged 24-50 individuals in each group, where diet effect on the lard composition was weighted using the PCs scores as covariates in a tri-factorial (genotype, carcass leanness, sex) covariance design (Piasentier et al, 2009). Rocchetti et al investigated the impact of different diets on the lipidomic profile of pork using 36 animals and applied both PCA and cluster analysis (Rocchetti et al, 2022). Petroman et al applied gas chromatography-mass spectrometry and PCA to evaluate the dissimilarity of Mangalitza lipid fractions in different layers of backfat with or without heat treatment (Petroman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the use of MS-based lipidomics for the identification and quantification of individual TAGs in animal-based foods. Rocchetti et al [76] employed MS-based lipidomics to monitor the alterations in lipid species in pigs fed two different diet supplements, n-3 fatty acids and polyphenols obtained from grape skin and oregano. They detected 1507 lipid molecules and 195 compounds matching the MS/MS spectra provided by the LipidBlast database, in which they found alterations in 32 TAG species when the pigs were fed two different diets.…”
Section: Tagsmentioning
confidence: 99%
“…Recently, lipidomics has been widely used in animal husbandry [11]. An increasing number of researchers have started to use lipidomics to identify the lipid composition of pork under different feeding strategies, such as the addition of vegetable oils [12], flaxseed [13], or microalgae [14] to diets, which are of great significance to identify the nutritional value of pork and investigate the effects of different lipids on metabolic regulation of the organism. Due to the influence of corn distillers dried grains with solubles on fatty acid composition and other aspects, we assumed that adding corn distillers dried grains with solubles to the diet could affect the composition and distribution of lipids in pork.…”
Section: Introductionmentioning
confidence: 99%